Iron gene expression profile in atherogenic Mox macrophages - Marques, L. (2020)
The role of macrophage iron in the physiopathology of atherosclerosis is an open question that needs to be clarified. In atherosclerotic lesions, recruited macrophages are submitted to cytokines and oxidized lipids which influence their phenotype. An important phenotypic population driven by oxidized phospholipids is the Mox macrophages which present unique biological properties but their iron phenotype is not well described.